Attachment of human endothelial cells to polyester vascular grafts: pre-coating with adhesive protein assemblies and resistance to short-term shear stress - Chlupáč, J; Filová, E; Riedel, T; Houska, M; Brynda, E; Remy-Zolghadri, M; Bareille, R; Fernandez, P; Daculsi, R; Bourget, C; Bordenave, L; Bačáková, L (Physiological research, 2014)
Cardiovascular prosthetic bypass grafts do not endothelialize spontaneously in humans, and so they pose a thrombotic risk. Seeding with cells improves their performance, particularly in small-caliber applications. Knitted tubular polyethylene-terephthalate (PET) vascular prostheses (6 mm) with commercial type I collagen (PET/Co) were modified in the lumen by the adsorption of laminin (LM), by coating with a fibrin network (Fb) or a combination of Fb and fibronectin (Fb/FN). Primary human saphenous vein endothelial cells were seeded (1.50 × 10(5)/cm2), cultured for 72 h and exposed to laminar shear stress 15 dyn/cm(2) for 40 and 120 min. The control static grafts were excluded from shearing. The cell adherence after 4 h on PET/Co, PET/Co +LM, PET/Co +Fb and PET/Co +Fb/FN was 22%, 30%, 19% and 27% of seeding, respectively. Compared to the static grafts, the cell density on PET/Co and PET/Co +LM dropped to 61% and 50%, respectively, after 120 min of flow. The cells on PET/Co +Fb and PET/Co +Fb/FN did not show any detachment during 2 h of shear stress. Pre-coating the clinically-used PET/Co vascular prosthesis with LM or Fb/FN adhesive protein assemblies promotes the adherence of endothelium. Cell retention under flow is improved particularly on fibrin-containing (Fb and Fb/FN) surfaces.
Keywords: Shear Strength; polyestery; Time Factors; Stress, Mechanical; Animals; skot; časové faktory; Humans; cévní protézy; Blood Vessel Prosthesis; Saphenous Vein; vena saphena; mechanický stres; Collagen Type I; Endothelial Cells; endoteliální buňky; zvířata; kolagen typu I; pevnost ve smyku; Cattle; Polyesters; lidé